Sărada Mahinda = Jan̲ātipati Mahinta Rājapakṣa = President Mahinda Rajapakse. (Koḷamba : Ministry of Mass Media & Information, 2011)
A collection of cartoons on Mahinda Rajapakse's first five year as Sri Lanka's president.
Sinhalese and English; includes some passages in Tamil.
Keywords: Presidents -- Sri Lanka -- Caricatures and cartoons